2001
DOI: 10.1364/ao.40.000821
|View full text |Cite
|
Sign up to set email alerts
|

In situ combustion measurements of CO_2 by use of a distributed-feedback diode-laser sensor near 20 µm

Abstract: High-resolution absorption measurements of CO 2 were made in a heated static cell and in the combustion region above a flat-flame burner for the development of an in situ CO 2 combustion diagnostic based on a distributed-feedback diode laser operating near 2.0 m. Calculated absorption spectra of hightemperature H 2 O and CO 2 were used to find candidate transitions for CO 2 detection, and the R͑50͒ transition at 1.997 m ͑the 1 ϩ 2 2 ϩ 3 band͒ was selected on the basis of its line strength and its isolation fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 12 publications
3
34
1
Order By: Relevance
“…The agreement is significantly improved if the comparison is constrained to include only those studies published since 1999, suggesting that the empirical intensities from the more recent studies are more consistent. For example, the comparisons shown for seven bands [29,34,[37][38][39][41][42][43][44] in Table 13 yield a mean difference within 0.6 % of the present values. However, our S v for the 20012-00001 band at 4977.8 cm À1 is 1.5% lower than reported by other recent studies, most of which measured a few lines with laser spectrometers.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…The agreement is significantly improved if the comparison is constrained to include only those studies published since 1999, suggesting that the empirical intensities from the more recent studies are more consistent. For example, the comparisons shown for seven bands [29,34,[37][38][39][41][42][43][44] in Table 13 yield a mean difference within 0.6 % of the present values. However, our S v for the 20012-00001 band at 4977.8 cm À1 is 1.5% lower than reported by other recent studies, most of which measured a few lines with laser spectrometers.…”
Section: Discussionsupporting
confidence: 42%
“…The results of the analysis of those line strengths are included in Table 2, except for some of the entries for which the authors provided only a small number of line strengths which were too few to analyze. The values of (o À c)% from these nominal studies [41][42][43][44][45] are included in last columns of Table 9 [41-43] and the last two columns of Table 11 [44,45]. The numbers for upper state J in Table 2 are often larger than the transitions shown in Tables 6-12.…”
Section: Resultsmentioning
confidence: 99%
“…These included the R26 transition of 20013 ‹ 00001 reported by Zeninari et al [9]; 21 transitions of 20012 ‹ 00001 reported by Corsi et al [10,11]; 3 R-branch transitions in 20012 ‹ 00001 by Webber et al [12]; 11 lines between P28 and R28 in 30013 ‹ 00001 by Hikida et al [13] and 10 lines between P20 and P2 in the 30013 ‹ 00001 band by De Rosa et al [14]. The most extensive laser data of 12 C 16 O 2 self-broadening were reported by Henningsen and Simonsen [15] who measured 38 transitions in the 30012 ‹ 00001 band from P20 to R52.…”
Section: Introductionmentioning
confidence: 99%
“…Because these high-resolution measurements had smaller uncertainties than those listed in HIT-RAN96, we consider the measured values to be an improvement. The measured line strengths for the CO 2 transition at 5007.787 cm Ϫ1 were previously published 12 and are listed in Table 2.…”
Section: Spectroscopic Resultsmentioning
confidence: 99%